Does acupressure therapy decrease blood pressure in hypertensive elderly? - Sang Ayu Ketut Candrawati; Ni Komang Sukra Andini (Pusat Penelitian dan Pengabdian Masyarakat (PPPM) STIKES Banyuwangi, 2025)
ntroduction: Hypertension is a high blood pressure condition often referred to as the